Omeprazole with Calcium Hydroxide’s Effectiveness as an Intracanal Medication against Enterococcus faecalis - Binila Surendra Babu; Souparnika Divakaran Padmini; Manthra Ajith Shreya; Panachiyil Rajan Sreekala; Renju Chanthiam; C Nisha (Journal of Pharmacy and Bioallied Sciences)
Aims: To evaluate the effectiveness of omeprazole mixed with calcium hydroxide (Ca(OH)2), as intracanal medicament in eliminating Enterococcus faecalis. Materials and Methods: Our study included 93 extracted mandibular premolars. A total of 15 μL of 0.5 McFarland standard E. faecalis (ATCC 29212) was inoculated into each canal and incubated at 36.5°C for 24 h. The specimens were divided into three groups: Group I (n = 30), control group without intracanal medicament, Group II (n = 30) with Ca(OH)2 and Group III (n = 30) with omeprazole and Ca(OH)2. The numbers of colony forming units (CFUs) were counted after 24 h. The same procedure was repeated after 7 and 14 days for the remaining samples. Statistical Analysis Use: Statistical analysis was performed using the analysis of variance (ANOVA) test (P < 0.05). Results: We found a significant reduction in the colony-forming unit count in the omeprazole– Ca(OH)2 group. In the Ca(OH)2 group, the number of CFUs was significantly higher than in the omeprazole–Ca(OH)2 group. Conclusion: Omeprazole mixed with Ca(OH)2 was more effective than Ca(OH)2 alone in eliminating E. faecalis.